The Influence Of Innovative Work Behavior And Work Environment On Employee Performance - Reza, Mela (Lentera Ilmu Nusantara, 2024)
This study aims to analyze the influence of innovative work behavior and work environment on employee performance at PT Kawasan MM 2100. Innovative work behavior includes idea generation, experimentation, and implementation of new ideas. Meanwhile, work environment encompasses work atmosphere, facilities, and employee relationships. The research utilized questionnaires distributed to 60 employees with diverse backgrounds. The results of multiple linear regression analysis demonstrated that innovative work behavior and work environment have a significantly positive effect on employee performance. This means employees who often generated and applied creative ideas tended to have higher performance. Likewise, a comfortable and innovation-supporting work environment also improves employee performance.The implications are that management needs to encourage an innovative culture and behavior by providing appreciation, training, and avenues for employees to express ideas. Management is also advised to provide an ergonomic work environment that builds relationships and collaboration among employees. This is believed to significantly increase employee contribution and productivity.